Efektivitas Bahan Ajar Berbasis Android terhadap Hasil Belajar - Wahyuni, Sri; Etfita, Fauzul (GERAM: Gerakan Aktif Menulis, 2019)
Learning material is one of the crucial elements that must be considered in learning. However, learning materials used are still conventional in the form of hardcopy and softcopy, so students are reluctant to read. Specifically, in the English for office course, simple and practical learning material is needed so that they can support both theory and practice. Related to this problem, the purpose of this study was to analyze the effect of android-based learning material on learning achomplisment and its effectiveness of the implementation of android-based learning materials in improving learning outcomes. The study was conducted at Universitas Islam Riau on students who took English for office courses. Through random sampling techniques determined the sample of the experimental class and the control class. Data was collected through pre-test and post-test distribution in the two sample classes. Based on several stages of data analysis, the data is normally distributed and the data variants are homogeneous. Furthermore, paired sample t-test, showing a significance value of 0.039 <0.05, it can be concluded that there are differences in the average learning outcomes for pre-test and post-test in the classes taught by applying android-based learningg materials. While the N-Gain score test revealed that the implementation of android-based learning material was quite effective to improve learning outcomes with a value of 63.00%. So it can be concluded that, there is an influence and quite effective android-based learning materials on learning achomplisment.